CBCT Assessment of Effectiveness of ProTaper Next and WaveOne file Systems on Remaining Dentin Thickness - Vathsala Nijalingappa; Umreena Zahoor Banday; Prabu Mahin Syed Ismail; Abinash Mohapatra; Gaurangi Lavania; Prajakta Ganesh Chougule (Wolters Kluwer Medknow Publications, 2024)
Introduction: Obturation of the canal space, efficient disinfection, and thorough canal debridement are essential components of endodontic therapy success. A crucial first step is biomechanical preparation. Objectives: This study set out to assess various file systems' cleaning efficacy in terms of the thickness of dentin that remained after cleaning. Materials and Method: Twenty permanently removed anterior teeth were used in the investigation, and they were split into two groups: Group B used reciprocating WaveOne file systems, and Group A used ProTaper Next (PTN). After obtaining a pre-CBCT scan, the corresponding file groups proceeded with biomechanical preparation. A post-CBCT scan was obtained, and the dentin thickness remaining was compared between the pre- and post-CBCT scans. Statistics were used to analyze the data. Result: Dentin thickness decrease was shown to be minimal for ProTaper Next (PTN) and maximal for WaveOne; nonetheless, the intergroup comparison was deemed to be highly inconsequential. Conclusion: After biomechanical preparation, WaveOne is a highly recommended rotary endodontic device that does not significantly reduce the residual dentin thickness.